Pseudoangiomatous stromal hyperplasia of the breast: a rare condition – from diagnosis to treatment - Assis, Julimar Rocha de; Nunes, Cristiana Buzelin; Lucena, Clécio Ênio Murta de (Mastology, 2021)
Pseudoangiomatous Stromal Hyperplasia (PASH) of the breast is a rare condition that consists of the proliferation of the breast myofibroblastic stromal cells, lining anastomosing vascular slit-like spaces. This condition is not considered a pre-malignant lesion and affects mainly premenopausal women. Its etiology is still uncertain, but its behavior points to a hormonal cause. It has a varied clinical presentation and can be diagnosed as an incidental finding of biopsies or with the manifestation of clinical signs and symptoms. As for the diagnosis, it can be performed with the correlation between clinical data, imaging and histopathological analysis. Due to its rare nature, there are still no prospective studies regarding treatment, but, in most cases, clinical and radiological follow-up is a safe strategy. The aim of this paper is to synthesize the data available in the literature about this condition, which, although benign in nature, can bring important aesthetic, musculoskeletal and psychological repercussions.